2019
DOI: 10.1109/access.2019.2903859
|View full text |Cite
|
Sign up to set email alerts
|

Triple-Classification of Respiratory Sounds Using Optimized S-Transform and Deep Residual Networks

Abstract: Digital respiratory sounds provide valuable information for telemedicine and smart diagnosis in an non-invasive way of pathological detection. As the typical continuous abnormal respiratory sound, wheeze is clinically correlated with asthma or chronic obstructive lung diseases. Meanwhile, the discontinuous adventitious crackle is clinically correlated with pneumonia, bronchitis, and so on. The detection and classification of both attract many studies for decades. However, due to the contained artifacts and con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
68
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(68 citation statements)
references
References 31 publications
(35 reference statements)
0
68
0
Order By: Relevance
“…The best results were achieved using a Convolutional Neural Network (CNN). Chen et al [9] proposed ResNet with an OST-based (Optimized S-Transform based) feature map to classify wheeze, crackle, and normal sounds. In detail, three RGB -maps (Red-Green-Blue) of the rescaled feature map is fed into ResNet due to the balance between the depth and performance.…”
Section: Respiratory Sounds Detectionmentioning
confidence: 99%
“…The best results were achieved using a Convolutional Neural Network (CNN). Chen et al [9] proposed ResNet with an OST-based (Optimized S-Transform based) feature map to classify wheeze, crackle, and normal sounds. In detail, three RGB -maps (Red-Green-Blue) of the rescaled feature map is fed into ResNet due to the balance between the depth and performance.…”
Section: Respiratory Sounds Detectionmentioning
confidence: 99%
“…However, despite achieving high levels of performance, these methods require additional feature extraction step for features such as time domain, time-frequency domain (Chen et al. 2019 ), hilbert-huang transform (HHT) (Serbes et al. 2013 ), melFrequency cepstral coefficients (MFCCs) (Bahoura 2009 ), wavelet transform coefficients (Kahya et al.…”
Section: Introductionmentioning
confidence: 99%
“…On ICBHI17 dataset, the highest accuracy of 83.2% was reported. Chen et al [ 7 ] used a S-transform-based approach coupled with deep residual networks to classify lung sounds: crackle, wheeze, and normal. In their study, the reported accuracy was 98.79%.…”
Section: Introductionmentioning
confidence: 99%